Adolescents' experiences of living with HIV and AIDS. - Black, Linda Anne (My University, 2009)
A growing body of research exists that examines the nature of i n tervent ions aimed at educa ting adolescents in t e rms of HIV and AIDS (Campbell, 2003; Campbell & McPhail, 2002; Van Dyk, 2001). However, there appears to be a grave pauci ty of l i t e rature that explor es the impact of HIV and AIDS on adolescents’ psychological and emotional functioning. Adolescents who live in the af t e rmath following the death of a parent, or parents often have to deal with rejection from thei r community, and are often confronted with significant emo t ional, educa tional and psycho-social challenges. These cha llenges continue to pose enormous threat to the development of a healthy s e lf-concept (Foster & Germann, 2002). These adolescents continue to be marginalized as their voices remain largely s i l e n t in contemporar y research . Using a combination of Art therapy, and narr ative creation, twenty-eight adolescents participated in a group intervention intended to facilitate, empower and encourage meaning making processes, and to f ac i l i t at e both oral and wr i t ten communica tion about the i r exper iences of living wi th HIV and AIDS. Findings suggest that while adolescents living with HIV and AIDS continue to have significant emotional, physiological, and social cha l lenges on a daily basis, their stories espouse great hope, determination and resilience.
Keywords: Adolescents; HIV; AIDS